Direct algorithms for solving some inverse source problems in 2D elliptic equations. (8th September 2015) - Abdelaziz, Batoul; Badia, Abdellatif El; Hajj, Ahmad El
Abstract: This paper deals with the resolution of some inverse source problems in the 2D elliptic equation from Cauchy data. Two types of sources are considered, pointwise sources and sources having compact support within a finite number of small subdomains. An identification direct algorithm, based on an algebraic approach, is proposed. This is a new result, as far as we know, except in the case which is already considered in El Badia and Ha-Duong (2000 Inverse Problems 16 651–63 ).